Glass Barriers : Constraints to Women's Small-Scale Cross-Border Trade in Cambodia and Lao PDR - Seror, Marlon; Record, Richard; Clarke, Julian (World Bank, Washington, DC, 2017)
Trade facilitation projects often assume indirect benefits for small-scale, cross-border traders. Recent studies have shown the challenges faced in Africa by this population, especially women, but it remains unknown in Cambodia and the Lao People's Democratic Republic, despite large trade facilitation investments. This paper fills this gap, thanks to an innovative mix of original qualitative and quantitative data from various checkpoints on the borders with Thailand and Vietnam. The quantitative data, collected in 2014, consist of an exhaustive list of trade-related border crossings during two to three days and a survey of 158 randomly selected small-scale, cross-border traders and brokers. The paper combines qualitative data and statistical techniques to shed light on the structure of the small-scale, cross-border trade economy, traders' and brokers' profiles, the challenges they face, and potential solutions, with a particular emphasis on gender. Key challenges pertain to taxation and poor infrastructures. Narrow roads, insufficient parking space, and restrictive border regulations on transportation means cause traffic jams and delays. These disproportionately affect women, who are more time constrained. Despite a rather moderate tax pressure, widespread informal payments erode traders' and brokers' willingness to comply with taxes. Women suffer from a higher tax rate and a tax schedule that deters them from upgrading to more profitable cross-border trade activities. Along with capital constraints, this finding may explain the lower share of women in small-scale, cross-border trade than among own-account workers and the self-employed, as evidenced by nationally representative data. The paper delineates policy implications and puts forward concrete steps.